Pursuing packrats: An evaluation of noninvasive detection methods for Neotoma. (15th December 2018) - Gooley, Aaron C.; Schauber, Eric M.
ABSTRACT: Woodrats ( Neotoma spp.) are imperiled in large swathes of the United States. Their populations have previously been monitored mainly through live‐trapping and sign surveys. However, these methods are labor‐intensive and either stress captured animals or limited by sign visibility and persistence. As noninvasive alternatives, we deployed baited camera traps and baited track plates to monitor eastern woodrat ( N. floridana ) presence along rocky outcrops at 4 woodrat reintroduction sites in southern Illinois, USA, during May 2013 (5 camera and track‐plate stations/site) and May and September 2014 (4 camera and track‐plate stations/site) to compare their effectiveness. During each deployment, camera traps detected woodrat presence at all 4 sites while track plates only detected presence at 2–3 sites. A greater proportion of camera traps than track plates recorded detections during each deployment. Camera traps required more person‐hours to deploy and retrieve, but resulted in more detections per hour effort than track plates. We conclude that baited camera traps are superior to baited track plates for detecting and monitoring woodrat presence. © 2018 The Wildlife Society. Abstract : We compared the effectiveness of baited camera traps and baited track plates for monitoring eastern woodrat presence along rocky outcrops. Baited camera traps were superior to baited track tubes because they consistently detected woodrat presence at each site and resulted in more detections per hour effort, even though they required more person‐hours to deploy and retrieve.